Green Synthesized Metal Oxide Nanoparticles Mediate Growth Regulation and Physiology of Crop Plants under Drought Stress - Nadiyah M. Alabdallah; Md. Mahadi Hasan; Inès Hammami; Azzah Ibrahim Alghamdi; Dikhnah Alshehri; Hanan Ali Alatawi (Plants, 2021)
Metal oxide nanoparticles (MONPs) are regarded as critical tools for overcoming ongoing and prospective crop productivity challenges. MONPs with distinct physiochemical characteristics boost crop production and resistance to abiotic stresses such as drought. They have recently been used to improve plant growth, physiology, and yield of a variety of crops grown in drought-stressed settings. Additionally, they mitigate drought-induced reactive oxygen species (ROS) through the aggregation of osmolytes, which results in enhanced osmotic adaptation and crop water balance. These roles of MONPs are based on their physicochemical and biological features, foliar application method, and the applied MONPs concentrations. In this review, we focused on three important metal oxide nanoparticles that are widely used in agriculture: titanium dioxide (TiO2), zinc oxide (ZnO), and iron oxide (Fe3O4). The impacts of various MONPs forms, features, and dosages on plant growth and development under drought stress are summarized and discussed. Overall, this review will contribute to our present understanding of MONPs’ effects on plants in alleviating drought stress in crop plants.